The Influence of Waitstaff Service Quality on Guest Satisfaction at the Restaurant of Hotel Atsari Parapat - Mhd Daud Siregar; Mhd Hirsan Hanafi; Setia Putra Hutabarat (Brilliant International Journal Of Management And Tourism, 2026)
Guest satisfaction is a key indicator of service success in the hospitality industry, where waiter service quality plays a crucial role in creating positive customer experiences. This study aims to examine the influence of waiter service quality on guest satisfaction at the Atsari Parapat Hotel Restaurant. A quantitative approach with an associative research design was employed to analyze the relationship between the variables. The sample consisted of 80 hotel guests selected through purposive sampling based on the criterion that respondents had received direct waiter service. Data were collected using a five-point Likert scale questionnaire that met validity and reliability requirements, with all items declared valid and Cronbach’s Alpha values exceeding 0.70. Data were analyzed using simple linear regression. The findings revealed the regression equation Y = 30.135 + 3.228X, indicating that waiter service quality has a positive effect on guest satisfaction. The t-test result showed a t-value of 5.157, exceeding the t-table value of 1.99085, with a significance level of 0.000 (<0.05), confirming a significant relationship. The coefficient of determination (R²) of 0.754 indicates that waiter service quality explains 75.4% of the variation in guest satisfaction, while the remaining 24.6% is influenced by other factors. The study concludes that improving waiter competencies, service standards, and supporting facilities is essential for enhancing guest satisfaction and strengthening customer loyalty in the hospitality industry.